Variabilidade sazonal, atividade antimicrobiana, fracionamento bio-guiado, isolamento e elucidação estrural dos prinicpais constituintes do óleo essencial de Lippia alba (Mill.) N. E. Brown - Barros, Francisco Maikon Corrêa de (2008)
Lippia alba (Mill.) N. E. Brown is a native medicinal plant of South America. Known popularly as false-melissa , its leaves and roots are used in the treatment of some illnesses, including some of infective etiology. The presence of essential oils, among other metabolites with recognized antimicrobial activity, can explain its medicinal use. This paper describes the chemical analyses and antimicrobial activity of the essential oils from Lippia alba at different seasons of the year, as well as the bio-guided fractionation, the isolation and the structure elucidation of its main constituents. Lippia alba was cultivated in São Luiz Gonzaga, RS, Brazil, and its leaves were collected in 2005 and 2006 in the middle period (January, April, July and October) of each season. A voucher specimen (SMDB n° 10.050) was deposited in the herbarium of the Department of Biology, UFSM. The extraction of the essential oils was performed by the hydrodistillation method of fresh leaves. The oils were analyzed by GC-MS and their constituents were identified by the comparison of Kovat s retention indexes and mass spectra with literature data. The essential oil was fractionated by CC over silica gel for the isolation of germacrene D-4-ol and linalool, both identified by GC-MS, 13C and 1H NMR, DEPT-135, COSY and HETCOR. The antimicrobial activity of the essential oils, fractions and isolated compounds were determined by the broth microdilution method. The essential oil showed qualitative and semi-quantitative variability in relation to the seasons of the year. The yield ranged from 0.3 to 0.6%, being lower in winter and higher in summer, autumn and spring. The essential oil was composed of monoterpenoids (69 - 84%) and sesquiterpenoids (6 - 24%), being most of them oxygenated and hidrocarbonated, respectively. Moreover, the major compounds (> 15%) were not the same between the years of the analysis. The seasonal variability influenced the antimicrobial activity of the essential oils. With the exception of P. aeruginosa, all other microorganisms were susceptible to the essential oil. The most sensitive ones were S. cerevisiae (MIC and MFC of 800 μg/mL for the oil obtained in January), S. aureus (MIC of 800 μg/mL and MBC of 1600 μg/mL for the oils obtained in April and July) and K. pneumoniae (MIC and MFC of 1600 μg/mL for the oil extracted in July). In view of the antimicrobial activity, winter and summer are the best seasons for the collection and extraction of essential oils. The bio-guided fractionation of the essential oil showed that the fractions containing greater amounts of oxygenates are more active than those containing hydrocarbon compounds. Germacrene D-4-ol presented activity against S. cerevisiae (MIC and MFC of 200 μg/mL), P. zopfii (MIC and MFC of 400 μg/mL) and S. aureus (MIC and MBC of 800 μg/mL), while linalool was inactive against the tested microorganisms up to 3200 mg/mL.